2010
DOI: 10.1007/s10895-010-0628-y
|View full text |Cite
|
Sign up to set email alerts
|

A Coumarin-Based Fluorescent Chemosensor for Zn2+ in Aqueous Ethanol Media

Abstract: A coumarin-based fluorescent chemosensor 1 for Zn(2+) was designed and synthesized. Compound 1 exhibits lower background fluorescence due to intramolecular photoinduced electron transfer. However, upon mixing with Zn(2+) in 30% (v/v) aqueous ethanol, a "turn-on" fluorescence emission is observed. The fluorescence emission increases linearly with Zn(2+) concentration in the range 0.5-10 micromol L(-1) with a detection limit of 0.29 micromol L(-1). No remarkable emission enhancement was, however, observed for ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The fluorescent intensity enhancement may be due to the coordination of free ligand to metal ions, thus reducing the loss of energy via radiationless thermal vibrations of the intra‐ligand excited states, and to an increase in the rigidity of the ligand . The fluorescence of the ligand was probably quenched by the occurrence of a photo‐induced electron transfer (PET) process due to the lone pair of electrons of the donor atoms in the ligand . The fluorescence emission intensity of the Schiff base increased upon complex formation with metal ions in the following order: zinc(II) ~ nickel(II) < copper(II) < manganese(II) < cobalt(II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescent intensity enhancement may be due to the coordination of free ligand to metal ions, thus reducing the loss of energy via radiationless thermal vibrations of the intra‐ligand excited states, and to an increase in the rigidity of the ligand . The fluorescence of the ligand was probably quenched by the occurrence of a photo‐induced electron transfer (PET) process due to the lone pair of electrons of the donor atoms in the ligand . The fluorescence emission intensity of the Schiff base increased upon complex formation with metal ions in the following order: zinc(II) ~ nickel(II) < copper(II) < manganese(II) < cobalt(II).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence emission intensity of the Schiff base increased upon complex formation with metal ions in the following order: zinc(II) ~ nickel(II) < copper(II) < manganese(II) < cobalt(II). The ligand shows higher selectivity toward cobalt(II) compared to the other metal ions, so we can expect that its coordination would alleviate PET more effectively and provide enhanced fluorescence on chelation …”
Section: Resultsmentioning
confidence: 99%
“…Structures and references of coumarin-derived chemosensors for Zn(II) ions be competent for detecting zinc pools in cultured rat pituitary (GH3) and hepatoma (H4IIE) cell lines (N. C. Lim et al, 2005). Coumarin 44 is a fluorescent sensor for Zn 2+ and exhibits lower background fluorescence due to intramolecular PET but upon mixing with Zn 2+ in aqueous ethanol, a turn-on fluorescence emission is observed (Su et al, 2010). Recently it was reported that a biscoumarin linked by bi-thiazole acted as a colorimetric receptor selectively for Zn 2+ .…”
Section: Coumarin-derived Fluorescent Chemosensors For Metal Ionsmentioning
confidence: 99%
“…On the other hand, coumarin dyes are an important class of fluorescent compounds and have been used to construct a variety of fluorescent probes and chemosensors owing to their excellent photophysical properties .…”
Section: Introductionmentioning
confidence: 99%